Economic Factors Affecting the Industry Group Index and Business Sector Index of the Stock Exchange of Thailand - Klaynarong, Pimmada; Saenchan , Lampang; Khamkong, Manad (Journal of Applied Statistics and Information Technology, 2024)
The purpose of this research is to examine the economic factors affecting The Stock Exchange of Thailand’s industry group index and sector index. The economic factors include the price of gold (GOLD), the price of crude oil (OIL), the Thai Baht to United States Dollar exchange rate (THB_USD), the consumer price index (CPI), and the rate of interest of the Bank of Thailand (RATE). The study was conducted using monthly data from January 2018 to December 2023, totaling 72 months. Data were divided into three sets: 1) before the Covid-19 outbreak of 2018, 2) during the Covid-19 outbreak of 2020, and 3) after the Covid-19 outbreak of 2022 - 2023, using multiple regression analysis based on generalized least squares. A significance level of 0.05 indicated that both the consumer price index (CPI) and the Thai Baht to United States Dollar exchange rate (THB_USD) were significantly related to the prices of industrial groups and business categories prior and after the outbreaks of COVID-19. In the event of a COVID-19 outbreak, the price of crude oil (OIL), the Thai Baht to United States Dollar exchange rate (THB_USD), and the rate of interest of the Bank of Thailand (RATE) will affect the price index of industry groups and business sectors.